Get a Lot for Less: Evaulation of the $1 Vacant Lot Pilot Program in Milwaukee's 15th Aldermanic District - (:unkn) unknown (My University, 2016)
Between July, 2014 and July, 2015, the city piloted a program in which City-owned vacant lots could be sold for $1 to adjacent homeowners exclusively in the 15th Aldermanic District. The focus of this research was to determine the effectiveness of the $1 lot program in revitalizing the neighborhoods within that District. Using a visual assessment, this research observed the condition of 26 vacant lots sold approximately one year prior to the assessment and scored them based on a unique set of factors including the presence of a fence (a proxy for defensible space) the presence of gardens, whether any improvements had been made, and a maintenance score of 1-3. The findings showed that the majority of new purchased vacant lots were unfenced and without gardens. The average maintenance score was 1.7 indicating the general maintenance level was good. Most vacant lots were not markedly improved, but were maintained at a level similar to, or better than, when they were owned by the City. Additionally, this research conducted telephone interviews with 18 of the 26 first program participants. Through these interviews, this research ascertained the motivation for the purchase, future plans for the lots, and if owners perceived benefits to themselves and/or their community. Significantly, the findings showed residents viewed the additional land as beneficial and appreciated being a stakeholder in the development options around them. The interviewees wanted the responsibility and control of adjacent vacant land. Expanded ownership incentivized continued investment in the area and reduced blight conditions. The increased space expanded territoriality, an aspect of defensible space, as well as decreased perceived crime rates, especially dumping and loitering. Program participants spoke of plans to utilize the additional land in unique and beneficial ways. The residents of the area are essential components of this grassroots revitalization effort, especially in the absence of top-down development plans. This research also examined the financial benefits of the program for the City of Milwaukee in the form of increased property taxes and decreased maintenance fees. Using the total number of vacant lots sold from July 1, 2014 through February 29, 2016, the total increase in property taxes was between $10,800 and $21,600. Total savings in maintenance fees was $46,080. Other benefits of the program include increased housing code compliance and increased payment of delinquent property taxes due to the program’s requirements. Overall, the program represents a small step in the right direction for revitalization efforts in the 15th Aldermanic District. However, the $1 Vacant Lot Pilot Program cannot alone solve the problem of land vacancy. More could be done by the City of Milwaukee to ensure there is an increase in homeownership in order to better absorb present and future vacant lots and incentivize further yard improvements.
Keywords: Milwaukee; Revitilization; Vacant Lots